2022
DOI: 10.1111/obr.13485
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sedentary behavior in Asian preschool‐aged children: A systematic review

Abstract: Summary This systematic review aims to identify the multilevel correlates of sedentary behavior (SB) and its sub‐domains among preschool‐aged children aged 0–7 years in Asia. We systematically searched for studies published from 2000 onwards using terms related to SB correlates and Asia in six databases. Eligible studies were observational and used quantitative methods to examine correlates of total, and domain‐specific SB (screen viewing [SV] and non‐screen‐based SB) in Asian children living in Asia. Two revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…However, a review of systematic reviews suggests that results of previous studies were less consistent and a large number of studies have not observed associations between environmental factors and PA among children and adolescents aged 1–18 years [ 26 ]. More importantly, the vast majority of previous studies have been conducted in Western countries [ 25 , 26 ], with few studies from Asia to date [ 14 , 31 ]. Across the world, the neighbourhood environment varies, and it changes rapidly; this may greatly influence the impact of neighbourhood factors on children’s behaviours [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a review of systematic reviews suggests that results of previous studies were less consistent and a large number of studies have not observed associations between environmental factors and PA among children and adolescents aged 1–18 years [ 26 ]. More importantly, the vast majority of previous studies have been conducted in Western countries [ 25 , 26 ], with few studies from Asia to date [ 14 , 31 ]. Across the world, the neighbourhood environment varies, and it changes rapidly; this may greatly influence the impact of neighbourhood factors on children’s behaviours [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that preschool children spend at least 180 min per day doing physical activity (PA), of which at least 60 min are moderate‐to‐vigorous intensity, and that the time of sedentary screen time is less than 1 h (WHO, 2019). However, previous studies have reported that most preschool children do not reach the recommended levels of PA (Chaput et al, 2017; Lahuerta‐Contell et al, 2021; Tucker, 2008) and spend excessively sedentary behavior, mainly devoted to screen time (Chen et al, 2022; Hinkley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%